2020
DOI: 10.1111/famp.12610
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Relationships between a Surviving Parent and Children in Widowed Families: A Systematic Scoping Review

Abstract: The death of a family member affects not only individual family members but also their relationships and interactions. Grief has been studied mostly as an intrapersonal experience. Adopting the family perspective, this systematic scoping review focused on parent–child relationships in widowed families so as to identify what is already known on this topic and the research gaps for future study. The review follows the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses extension for Scoping Review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…However, we identified family-level risk factors (i.e., maternal depressive symptoms, poor quality mother-child communication) that predicted lower self-worth. This study adds to a small body of literature examining bereavement from a family systems perspective and highlights the importance of considering multiple family subsystems when seeking to understand bereavement experiences (Jiao et al, 2021;Morris et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…However, we identified family-level risk factors (i.e., maternal depressive symptoms, poor quality mother-child communication) that predicted lower self-worth. This study adds to a small body of literature examining bereavement from a family systems perspective and highlights the importance of considering multiple family subsystems when seeking to understand bereavement experiences (Jiao et al, 2021;Morris et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…Yet this particular family was able to demonstrate emotional strength. Grieving families are affected by loss based on the emotional integration of the family at the time of loss; (Bowen, 2004) and despite the devastating experience, there might be a potential for family members’ growth (Walsh, 2006) and improved relationships (Jiao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Loss affects both individuals and relationships among the individuals. Both individual and relational factors should be studied because family members grieve in the family even if there are individual differences among family members (Gilbert, 1996; Jiao et al, 2020). Nevertheless, there are not many studies that focus on both family and individual experiences of loss.…”
Section: Introductionmentioning
confidence: 99%
“…These empirical studies indicated the role of parent-child interactions in bereavement adjustment. However, as summarized in a recent systematic review, previous studies focused more on the parent's influence on children, while mutual interactions in the process of a widowed family coping and its influence on both parent and children are still less explored (Jiao et al, 2021).…”
mentioning
confidence: 99%